Pemanfaatan Ruang Masjid Suatu Kajian: Aktivitas Keagamaan Untuk Mengoptimalkan Peran dan Fungsi Masjid - Muh Alfian Hayadi; Muh Nasrun; Muh Arqam Harbi; Sam'un Mukramin (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
Mosques are one of the important institutions in the Islamic religion and have a major role in the lives of Muslims. Apart from being a place of worship, explore the use of mosque space in religious activities. Observing the Nur Ichsan Mosque, District Land Office. Gowa, this research highlights the role of social, religious education, as well as the importance of the role and function of mosques in Muslim society. Field research with a qualitative approach, involving observations, interviews and case studies at the Nur Ichsan Mosque. Data analysis was carried out to understand the use of mosque space and the role of administrators in increasing religious activities. Highlighting the mosque space as the main center of worship, its social role, religious education, and the importance of mosque administrators in optimizing the function of the mosque. The paper review supports discussion of the central role of mosques in Islam and management strategies to maximize the role of mosques. Mosques have a central role in religious activities, religious education and social welfare. Through the case study of the Nur Ichsan Mosque, this conclusion supports the use of mosque space as a center for activities that are beneficial for Muslims and society. This journal discusses the importance of utilizing mosque space for religious activities as well as the role of effective management in maximizing the function of mosques in society.